On the forbidden and the optimum crystallographic variant of rutile in garnet. Issue 6 (24th October 2016) - Hwang, Shyh-Lung; Shen, Pouyan; Chu, Hao-Tsu; Yui, Tzen-Fu
Abstract : This article reports on the critical structural factors dictating the selection of optimum crystallographic orientation relationship in a structurally complicated system such as the rutile–garnet system. Abstract : In many inclusion–host systems with similar oxygen packing schemes, the optimum crystallographic orientation relationship (COR) between the inclusion and the host is mostly determined by matching the similar oxygen sublattices of the two structures. In contrast, the prediction of the optimum COR or even just the rationalization of the observed COR(s) between an inclusion and host with incompatible oxygen sublattices, like rutile–garnet, is not straightforward. The related documentation for such cases is therefore limited. Given the abundant crystallographic data for the rutile–garnet system acquired by transmission electron microscopy and electron backscatter diffraction methods recently, this problem can now be examined in detail for the critical structural factors dictating the selection of optimum COR in such a structurally complicated system. On the basis of the unconstrained three‐dimensional lattice point match and structural polyhedron match calculated for the observed CORs, it becomes clear that the prerequisite of optimum COR for rutile (rt) in garnet (grt) is to have most of their octahedra similarly oriented/inclined in space by aligning ⟨103⟩rt and ⟨111⟩grt for needle extension growth. Further rotation along the ⟨103⟩rt //⟨111⟩grt direction then leads to the energetically most favorable COR‐2 variant with a good lattice point match defined by the coincidence site lattice (CSL) and a good topotaxial match of the constituent polyhedra at the CSL points, leaving unfavorable COR‐1′ in the forbidden zones. This understanding sheds light not only on hierarchical energetics for the selection of inclusion variants in a complicated inclusion–host system, but also on yet‐to‐be‐explored [ UVW ]‐specific CORs and hetero‐tilt boundaries for composite materials in general.